PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT MOMENTUM OTOMASI INDONESIA - Brigida Endah Nuraeni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The purpose of this research is to identify the influence of leadership and compensation on employee performance of PT Momentum Otomasi Indonesia. Sample of the research were 70 respondents. Validity test, reability test, multiple regression analysis, hypothesis test and coefficient determinant test with SPSS version 20 were done. The results showed that leadership not significantly towards on employee performance, and compensation has positively and significantly associated with employee performance. F test also showed that leadership and compensation simultaneously have significant influence on employee performance. Additional analysis suggests that compensation has the greatest effect and significant on employee performance (t.value = 5,117).